Assessment of root canal morphology of mandibular first molar in Indian population - Dhawan, Rajan; Singh Mann, Navjot; Dhawan, Shivani; Dahiya, Surya; Chugh, Chitral; Dhawan, Jayata (International Journal of Psychosocial Rehabilitation, 2020)
Background: The morphology of the root canal systems of mandibular molars may vary according to ethnic differences and origin, age, gender, and study design. The present study was conducted to assess root canal morphology of mandibular first molars in the Indian population.Materials & Methods: The present in invitro study was conducted on 120 extracted mandibular first molars (MFMs). Root canal curvature was assessed according to Schneider’s method. The samples were evaluated using a stereomicroscope under 10X magnification. The number of root canals, the type of canals based on Vertucci’s classification, and the isthmii at the distances of 2, 4, and 6 mm from the apex were recorded for each tooth.Results: Mesial roots had 2 canals in 100% of samples, and distal roots had 1 in 65% and 2 in 35%. The most common canal morphology was type IV in 50%, type II in 41%, type III in 6.5%, and type V in 2.5% in the mesial root and type I in 62%, type II in 24%, type IV in 9%, type III in 3%, and type V in 2% in the distal canal. The mean length of the mesial root was 15.4 mm, the distal root was 15.1 mm, and the disto-lingual root was 8.2 mm. In the mesial root, isthmii 2 mm from the apex were seen in 22%, at 4 mm in 45%, and at 6 mm in 33%. At the distal root, 34% at 2 mm, 36% at 4 mm, and 30% at 6 mm.Conclusion: Authors found that the most common mandibular first molar morphology in the mesial root was type IV and in the distal root was type .